Bioactive constituents and medicinal importance of genus Alnus - Sati, Sushil Chandra; Sati, Nitin; Sati, O. P. (Pharmacognosy Reviews, 2011)
The genus Alnus has been reviewed for its chemical constituents and biological activities including traditional importance of some common species. The plants of this genus contain terpenoids, flavonoids, diarylheptanoids, phenols, steroids, and tannins. Diarylheptanoids are the dominant constituents within the genus Alnus, few of them exhibited antioxidant effects and inhibitory activity against nuclear factor kappaB activation, nitric oxide and tumor necrosis factor-α production, human umbilical vein endothelial cells, farnesyl protein transferase, cell-mediated low-density lipoprotein oxidation, HIF-1 in AGS cells, and the HIV-1-induced cytopathic effect in MT-4 cells. Some ellagitannines showed hepatoprotective activity even in a dose of 1 mg/kg which is ten-fold smaller compared with the dose of traditional flavonoid-based drugs. The members of genus Alnus are well known for their traditional uses in the treatment of various diseases like cancer, hepatitis, inflammation of uterus, uterine cancer, rheumatism, dysentery, stomachache, diarrhea, fever, etc. The aim of the present review is to summarize the various researches related to the chemistry and pharmacology of genus Alnus.
Keywords: Alnus; antioxidant effects; diarylheptanoids; HIV-I; inhibitory activity